Effects of Majorana physics on the UHE ντ flux traversing the Earth - Duarte, Lucía (2017)
We study the effects produced by sterile Majorana neutrinos on the ντ flux traversing the Earth, considering the interaction between the Majorana neutrinos and the standard matter as modeled by an effective theory. The surviving tau-neutrino flux is calculated using transport equations including Majorana neutrino production and decay. We compare our results with the pure Standard Model interactions, computing the surviving flux for different values of the effective lagrangian couplings, considering the detected flux by IceCube for an operation time of 10 years, and Majorana neutrinos with mass mN∼ mτ.